Unveiling the Dynamics of Financial Literacy and Inclusion in Women Digital Loan Decision Making - Riwayati, Hedwigis Esti; Rachman, Hikmah Abdul; Pramesworo, Septo; Yustisia, Natali; Umar, Haryono; Siahaan, Magda (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study examines the role of lifestyle in mediating the influence of financial literacy and financial inclusion on the decision to take online loans. This research was conducted on women who use online loans in Indonesia. The sampling method used nonprobability sampling, with the respondents being 200 Indonesian women who used online loans. Data analysis uses Partial Least Square (PLS) to test the direct and indirect effects of financial literacy and financial inclusion on online loan decision-making. The results show that financial literacy, inclusion, and lifestyle significantly positively affect online loan decision-making. Financial literacy does not affect lifestyle, while financial inclusion significantly affects women's lifestyles in Indonesia. Lifestyle cannot mediate the influence of financial literacy and financial inclusion on women's online loan decision-making in Indonesia. The results of this study emphasize the importance of financial literacy and inclusion in shaping good financial behavior, especially in making decisions to apply for loans. Efforts to increase financial literacy and access to financial inclusion can be the primary strategy to improve the financial behavior of women in Indonesia in online loan decision-making.